ANALISIS IMBAL HASIL PADA PRODUK BERAKAD BAGI HASIL PERBANKAN SYARIAH INDONESIA - Ak, Yohani SE,. M.Si (Majalah Neraca, 2011)
This research has a purpose to analyze the deferences of return sharing product Â at indonesian islamic banking. The statistic method used to test on the research hypothesis is Independent t test. To analyzed the data using secondary data. Â Sample of this research consist two bank, Sharia Mandiri Banking and Muammalat Banking. Its listed at www,muamalatbank.com and www.syariah mandiri.co.id from Â 2002 â 2010 with times series.Â The result of these study with level of significance 5% independent t test show that: (1) return between of Muamalat Banking and Syariah Mandiri Banking statistically itâsnot different significantly. Its mean that the return Â for sharia product is not influenced by the history and the old age of Islamic banks.Keyword : Sharia Product, Return, ROE